2023
DOI: 10.1101/2023.01.25.525534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aminobenzoic acid derivatives obstruct induced fit in the catalytic center of the ribosome

Abstract: TheEscherichia coliribosome can incorporate a variety of non-L-α-amino acid monomers into polypeptide chains, but with poor efficiency. Although these monomers span a diverse set of compounds, there exists no high-resolution structural information regarding their positioning within the catalytic center of the ribosome, the peptidyl transferase center (PTC). Thus, details regarding the mechanism of amide bond formation and the structural basis for differences and defects in incorporation efficiency remain unkno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Although the structure of the PylRS variant FRSA bound to 2-benzylmalonate 27 provides an explanation for the absence of enantio-preference at the aaRS level, the preference for D-like (S)-β 2 -OH 3 in the PTC was a surprise. Metadynamics simulations and recent cryo-EM structures 46 provide evidence that the preference for tRNA charged with (S)-β 2 -OH 3 has less to do with inherent stereochemistry than with differences in the ability to induce conformational changes within the PTC necessary for favorable bond formation. A better understanding of the interactions necessary to facilitate P-site electrophile deshielding could be used to identify D-α-amino acids that are successfully elongated in vivo, another long-sought goal.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the structure of the PylRS variant FRSA bound to 2-benzylmalonate 27 provides an explanation for the absence of enantio-preference at the aaRS level, the preference for D-like (S)-β 2 -OH 3 in the PTC was a surprise. Metadynamics simulations and recent cryo-EM structures 46 provide evidence that the preference for tRNA charged with (S)-β 2 -OH 3 has less to do with inherent stereochemistry than with differences in the ability to induce conformational changes within the PTC necessary for favorable bond formation. A better understanding of the interactions necessary to facilitate P-site electrophile deshielding could be used to identify D-α-amino acids that are successfully elongated in vivo, another long-sought goal.…”
Section: ■ Discussionmentioning
confidence: 99%
“…45 Indeed, recent cryo-EM structures of E. coli ribosomes with aminobenzoic acid monomers in the A-site show U2585 locked in the uninduced conformation, prohibiting access to the P-site peptidyl-tRNA. 46 Overall, the decreased pairwise distances within the RRM containing 4-acyl-tRNA fMet may indicate an inability to support the dynamic movements necessary for efficient bond formation. These differences in RRM structure provide a second explanation for the observed in vivo enantioselective preference for (S)-β 2 -OH 3 over (R)-β 2 -OH 4.…”
Section: Mapylrsmentioning
confidence: 99%
See 1 more Smart Citation
“…295 Recent cryo-EM structures and molecular dynamic simulations of various 2-Abz derivatives within the PTC have indicated that their nucleophilic amine is located 4 Å or more away from the P site carbonyl and that their relatively rigid aromatic backbone sterically occludes optimal fit into the A and P sites, potentially disrupting the proton transfer chain. 296,297 These issues may contribute to the poor translational efficiency of these npMs. 296,297 Katoh and Suga used tRNA Pro1E2 CGG to perform single incorporation of 2-Abz and seven other derivatives into rP1-(npM) 1 at the CCG codon.…”
Section: Impact Of Ef-p On Elongation Of Nonproteinogenic Monomersmentioning
confidence: 99%
“…296,297 These issues may contribute to the poor translational efficiency of these npMs. 296,297 Katoh and Suga used tRNA Pro1E2 CGG to perform single incorporation of 2-Abz and seven other derivatives into rP1-(npM) 1 at the CCG codon. 295 Inclusion of EF-P increased translation efficiency, ranging from 1.4-fold to 6.8-fold.…”
Section: Impact Of Ef-p On Elongation Of Nonproteinogenic Monomersmentioning
confidence: 99%